Vagus Nerve Stimulation in Rodent Models: An Overview of Technical Considerations - Noller, Crystal M.; Levine, Yaakov A.; Urakov, Timur M.; Aronson, Joshua P.; Nash, Mark S. (Frontiers in Neuroscience, 2019)
Over the last several decades, vagus nerve stimulation has evolved from a treatment for select neuropsychiatric disorders to one that holds promise in treating numerous inflammatory conditions. Growing interest has focused on the use of vagus nerve stimulation for other indications, such as heart failure, rheumatoid arthritis, inflammatory bowel disease, ischemic stroke, and traumatic brain injury. As pre-clinical research often guides expansion into new clinical avenues, animal models of vagus nerve stimulation have also increased in recent years. To advance this promising treatment, however, there are a number of experimental parameters that must be considered when planning a study, such as physiology of the vagus nerve, electrical stimulation parameters, electrode design, stimulation equipment, and microsurgical technique. In this review, we discuss these important considerations and how a combination of clinically-relevant stimulation parameters can be used to achieve beneficial therapeutic results in pre-clinical studies of sub-acute to chronic vagus nerve stimulation, and provide a practical guide for performing this work in rodent models. Finally, by integrating clinical and pre-clinical research, we present indeterminate issues as opportunities for future research.